Information About Inequality of Opportunity Increases Downward Mobility Perceptions: A Population-Wide Randomized Survey Experiment - Gugushvili, Alexi (Frontiers in Psychology, 2022)
Existing evidence which is primarily based on cross-sectional and observational data suggests that perceptions of doing worse or better than parents might be more important for various life outcomes than the conventional measures of mobility based on the objective indicators of socioeconomic position. In 2021, we commissioned a nationally representative survey in the Republic of Georgia which included a population-wide randomized survey experiment. We confirmed the association between, on the one hand, perceived social mobility and, on the other hand, physical and mental health, satisfaction with life, and the perceived state of affairs in the country. More importantly, the experimental design allowed us to conclude that the perception of being downwardly mobile was causally determined by a short message shared with individuals that equality of opportunity in their country was low. Those who were given information that children’s socioeconomic position was strongly linked to their parents’ socioeconomic position were seven percentage points more likely than individuals in the control group to perceive themselves as being downwardly mobile. We extrapolate these findings to the broader context and argue that the messages about (in)equality of opportunity which individuals receive in their everyday lives might also shape their perceptions of social mobility in other countries.